The effectiveness of giving lemon aromatherapy to reduce the frequency of emesis gravidarum in pregnant women - Idawati; Novita, Widiya; Pusvita, Henny; Susanti, Heri; Intan, Meurah (International Journal on ObGyn and Health Sciences, 2023)
Background: Emesis gravidarum is astate of nausea sometimes accompanied by vomiting that occurs in early pregnancy. These symptoms usually occur 6 weeks after the first day of the last menstrual period and last approximately 10 weeks, but in some cases can continue until the second and third trimester of pregnancy. About 50-90% of pregnant women experience complaints of nausea and vomiting. This complaint is usually accompanied by hypersalivation (excessive salivation), headaches, flatulence, and weakness in the body. These complaints are commonly known as "morning sickness". The frequency of morning sickness is not only in the morning but can be day and even night. Hormonal changes in each pregnant woman will respond differently, so not all experience nausea vomiting. Objective: to examine more deeply the effectiveness of lemon aromatherapy on reducing the frequency of nausea and vomiting (emesis gravidarum) in pregnant women who are in accordance with previous studies by reviewing several studies. Method: This study uses several sources including searching several journals through (Google Shcoolar) with the Literature review method. The results of statistical analysis: that there is an effect of lemon aromatherapy on emesis gravidarum. Bottom Line: Lemon is an effective aromatherapy for reducing nausea and vomiting in pregnant women with emesis gravidarum.